Libertine Enlightenment
XI, 256 p.
Keywords: Sex in the Eighteenth-century was not simply a pleasure; it had profound philosophical and political implications. This book explores those implications, and in particular the links between sexual freedom and liberty in a variety of European and British contexts. Discussing prostitutes and politicians, philosophers and charlatans, confidence tricksters and novelists, Libertine Enlightenment presents a fascinating overview of the sexual dimension of enlightened modernity.